Assessment of Quality of Life in Acne Vulgaris Using WHOQOL-BREF - Acharya, Asmita; Giri, Uma; Shrestha, Rushma; Regmi, Bidhi; Ray, Radhe Shyam; Sitaula, Sabina; Dhakal, Shishan (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Background: Acne is a common dermatological condition that significantly affects quality of life. The impact of acne extends beyond physical symptoms, influencing psychological, social, and environmental aspects of life. This study utilizes the World Health Organization Quality of Life-BREF (WHOQOL BREF) instrument to assess the quality of life in individuals with acne, aiming to understand the broader implications of this condition across various domains. Materials and Methods: A hospital-based cross-sectional observational study was conducted, recruiting a total of 130 patients with acne vulgaris. QOL was measured using the WHOQOL-BREF questionnaire. The Nepali and English version of WHOQOL-BREF was used depending on the comfort of participants. The data was collected using a preformed proforma. The analysis of results was done using percentage, mean ± standard deviation, correlation coefficient where appropriate. Results: A total of 130 participants with acne, female (65.4%) and male (34.6%) were included in the study. The mean scores for the WHOQOL BREF domains were as follows: Physical (61.52), Psychological (58.57), Social (61.23), and Environmental (60.95), with the psychological domain being mostly affected by acne. There was a weak negative correlation between acne severity and various domains. Conclusion: The study highlights that acne affects various aspects of quality of life, with the most substantial impact seen in the psychological domain. Understanding the quality of life in individuals with acne is crucial for developing comprehensive treatment approaches that address not only the physical but also the psychological, social, and environmental factors associated with the condition. These findings suggest the importance of a holistic approach in managing acne, emphasizing the need for supportive interventions to improve overall well-being.